Real Time Energy Monitoring & Current Spikes Detection System For Enhanced Energy Conservation In Residential Area - Ismail, Muhammad Luqman; Norain Sahari (Progress in Engineering Application and Technology, 2024)
In a time of relentless technological advancement, the use of electric equipment is rising at a rate exponentially. The need for power has rose to levels never seen before. As our reliance on electronic conveniences grows, so does the demand for a detailed understanding of energy consumption. Thus, this project aims to propose a simple prototype of a energy monitoring system enabling real time monitoring and current spikes detection, to detect to unexpected surges in power specifically for home user. The project focuses on building a reliable hardware system using the ESP32 microcontroller, ZMPT101B voltage sensor, and SCT013-030 current sensor. This integrated system is designed for the real time monitoring of energy consumption, with communication facilitated through the cloud via the ThingSpeak platform for IoT. The ESP32 microcontroller functions as the central processing unit. The ZMPT101B operates to measure voltage, and the SCT013-030 monitors current flow. Utilizing the ThingSpeak platform, the system actively transmits data to the platform. The mobile application mirrors the data from the platform and this ensures users have a seamless interface for vigilant oversight of energy usage. The system able to monitor voltage, current, energy consumption, bill estimation and identified current spikes. In nutshell, the accomplishment of the system is marked by its ability to achieve the objective of creating an integrated system for monitoring energy consumption in residential areas and calculating estimation bills. The system demonstrates acceptable accuracy, with the highest observed error difference standing at 12.438%, all achieved through a low-cost implementation. Consequently, the project is deemed successful in meeting its predefined goals and delivering a functional solution for real-time energy monitoring and billing estimation in residential settings.